2021
DOI: 10.1039/d1ee01957k
|View full text |Cite
|
Sign up to set email alerts
|

A donor polymer based on 3-cyanothiophene with superior batch-to-batch reproducibility for high-efficiency organic solar cells

Abstract: A donor polymer based on 3-cyanothiophene, a structurally simple unit, is synthesized for organic solar cells, which exhibited prominent power conversion efficiency and excellent batch-to-batch reproducibility in a wide molecular weight range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 61 publications
0
78
1
Order By: Relevance
“…As shown in Figure 3 a , the ratio of electron mobility and hole mobility was determined as 5.3 without 2PACz in BHJ, while the value was optimized to 1.3 with the addition of 3 wt% 2PACz, partly accounting for the higher FF in 2PACz modified device. [ 59,60 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 3 a , the ratio of electron mobility and hole mobility was determined as 5.3 without 2PACz in BHJ, while the value was optimized to 1.3 with the addition of 3 wt% 2PACz, partly accounting for the higher FF in 2PACz modified device. [ 59,60 ]…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3a, the ratio of electron mobility and hole mobility was determined as 5.3 without 2PACz in BHJ, while the value was optimized to 1.3 with the addition of 3 wt% 2PACz, partly accounting for the higher FF in 2PACz modified device. [59,60] A stronger build-in electric field across the device is expected to attenuate space charge effects and effectively sweep-out the free charges. [36] In order to quantitate the impact of 2PACz on the built-in electric field, the capacitance-voltage (C-V) measurements were conducted in dark environment.…”
Section: Charge Generation Recombination and Extractionmentioning
confidence: 99%
“…Poly(3-hexylthiophene) (P3HT) was one of the most important donor materials in the history of organic PVs. It has a simple molecular structure, and thus, is easy and cheap to synthesize [16][17][18][19][20] , which are the paramount evaluation criteria for the scaling-up of OSCs. It has been reported that the synthesis of over 10 kg P3HT could be realized in a single batch, making it the most scalable donor material 21 .…”
Section: Introductionmentioning
confidence: 99%
“…[7,[56][57][58][59][60] State-of-the-art polymer donors, PM6, P2F-EHp, D18, etc., containing a BDT unit, have shown unprecedented progress in NFA-based PSCs (NFA-PSCs) (Figure 1). [52,53,[61][62][63][64][65][66][67][68][69][70][71][72][73] Moreover, a number of high-efficiency donor polymers also have been explored without the BDT unit, such as PTQ10, PBTATBT-4f, etc. However, its furan analogue, benzo[1,2-b:4,5-b 0 ]difuran (BDF), which possesses a smaller size than the BDT unit and thus generates weaker steric hindrance to adjacent units and tighter packing arrangement, is less developed as an efficient building block for the polymer donors.…”
Section: Introductionmentioning
confidence: 99%